Acoustics of bangla speech sounds - Datta, Asoke Kumar 1934- (Springer, 2018)
This book presents the consolidated acoustic data for all phones in Standard Colloquial Bengali (SCB), commonly known as Bangla, a Bengali language used by 350 million people in India, Bangladesh, and the Bengali diaspora. The book analyzes the real speech of selected native speakers of the Bangla dialect to ensure that a proper acoustical database is available for the development of speech technologies. The acoustic data presented consists of averages and their normal spread, represented by the standard deviations of necessary acoustic parameters including e.g. formant information for multiple native speakers of both sexes. The study employs two important speech technologies:(1) text to speech synthesis (TTS) and (2) automatic speech recognition (ASR). The procedures, particularly those related to the use of technologies, are described in sufficient detail to enable researchers to use them to create technical acoustic databases for any other Indian dialect. The book offers aunique resource for scientists and industrial practitioners who are interested in the acoustic analysis and processing of Indian dialects to develop similar dialect databases of their own.